2014
DOI: 10.1007/s40609-014-0011-z
|View full text |Cite
|
Sign up to set email alerts
|

Bi-directional Exchange: the Cornerstone of Globally Focused Social Work

Abstract: Social work holds a unique place relative to other professions in that it prioritizes the elimination of human suffering as its primary goal. The roots of the profession are firmly planted in Western theories, historically and culturally specific perspectives, and knowledge. History has repeatedly demonstrated an association between the arrival of Westerners and the subsequent control of natural resources. Some argue that the development of global social work practice has serious pitfalls, including diverting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…There are large gaps between evidence-based practices, community services/resources, and primary care services ( Brownson et al 2014 ; Brookman-Frazee et al 2015 ; Jenkins et al 2013 ). There is a need to strengthen social work practice and offer a better integration of social work services in primary care setting ( Parker et al 2014 ; Muga and Jenkins 2008 ). During the MCH facility interviews, we found that there were no social workers attached to the facility.…”
Section: Discussionmentioning
confidence: 99%
“…There are large gaps between evidence-based practices, community services/resources, and primary care services ( Brownson et al 2014 ; Brookman-Frazee et al 2015 ; Jenkins et al 2013 ). There is a need to strengthen social work practice and offer a better integration of social work services in primary care setting ( Parker et al 2014 ; Muga and Jenkins 2008 ). During the MCH facility interviews, we found that there were no social workers attached to the facility.…”
Section: Discussionmentioning
confidence: 99%
“…Embedding attributes like reciprocity into the framework of learning abroad experiences is difficult to attain or even pursue in contexts marred by limited, if any, resources and overworked individual program champions. When commitments to reciprocity remain overlooked, potentially sending organisations can fall back on established relationships, making the most of the goodwill afforded by host organisations (Parker, Ali, Ringell, & McKay, 2014), particularly in relation to risk management.…”
Section: Discussionmentioning
confidence: 99%
“…Various strategies can be adopted to decentralize these long-lasting practices. The partnerships should prioritize and invest in a bi-directional exchange and learning model that steps away from privileging and solely valuing Western paradigms, knowledge, and practices, and engage in true collaboration with partners from the South that respects, adopts, and learns from the knowledge, expertise, and values of the local partners (Parker et al 2014). Collaborative processes can become the foundation for new solutions to serious global problems (McKay and Paikoff 2007;Sperber et al 2008) and should be based on the following five core principles: (1) agreement and investment in shared goals; (2) equitable distribution of power, including fair involvement in decisionmaking and opportunities to change aspects of the action plan;…”
Section: Equity Collaboration Empowerment: a Human Rights Approachmentioning
confidence: 99%